ARCHITECTURAL RESTORATIONS IN CHILE IN THE 1950S: THEORY AND METHOD - Correa-Baeriswyl, M (EDITORA UNISINOS, 2025)
This article addresses the first architectural restoration projects conducted in Chile. Works were overseen by the National Monuments Council (NMC) and funded by the first historic monument repair budget, allocated by the State in the mid-twentieth century. The study offers a review of works carried out between 1950 and 1954. Previously unpublished documents from the NMC archive provide meeting minutes and progress reports relating to these pioneering works, and analysis reveals that the early interventions of the 1950s were conducted in line with prevailing thought concerning restoration of monuments to the past. More specifically, this study addresses the connections between these restoration works and the fundamental concepts of the discipline as set out in the Athens Charter of 1931. This, the first international treatise of its kind, came to shape the development of the discipline during the first half of the twentieth century in Europe, and its influence reached even as far as the distant continent of Latin America.